1992
DOI: 10.1007/bf00015618
|View full text |Cite
|
Sign up to set email alerts
|

Variation of elastic T-stresses along slightly wavy 3D crack fronts

Abstract: The non-singular terms in the series expansion of the elastic crack-tip stress field, commonly referred to as the elastic T-stresses, play an important role in fracture mechanics in areas such as the stability of a crack path and the two-parameter characterization of elastic-plastic crack-tip deformation. In this paper, a first order perturbation analysis is performed to study some basic properties of the T-stress variation along a slightly wavy 3D crack front. The analysis employs important properties of Buec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Equation 101 implies in particular that the average variation δσ x x + δσ zz is zero whatever the perturbation of the crack front; this means that at a given point of the broken region of the crack plane, the average 2D trace of the stress tensor, σ x x + σ zz , is independent of the position and shape of the crack front. This remarkable property is noted here in the special case of a semi-infinite crack, but was shown by Gao [1992] to in fact hold for any planar crack of arbitrary contour in some infinite body.…”
Section: Elements Of Rice and Bueckner's 3d Weight Function Theorymentioning
confidence: 53%
See 3 more Smart Citations
“…Equation 101 implies in particular that the average variation δσ x x + δσ zz is zero whatever the perturbation of the crack front; this means that at a given point of the broken region of the crack plane, the average 2D trace of the stress tensor, σ x x + σ zz , is independent of the position and shape of the crack front. This remarkable property is noted here in the special case of a semi-infinite crack, but was shown by Gao [1992] to in fact hold for any planar crack of arbitrary contour in some infinite body.…”
Section: Elements Of Rice and Bueckner's 3d Weight Function Theorymentioning
confidence: 53%
“…In physical terms, even though σ x x + σ zz , at a given, fixed point of the broken region of the crack plane, is independent of the position and shape of the crack front, evaluating the variation of T 11 + T 33 implies following the point of observation of σ x x + σ zz as the front moves, which inevitably entails a variation of this quantity. Gao. Gao [1992] did not consider only the case of an initially straight crack front as in the present work, but also that of a circular one.…”
Section: The Influence Of Imperfections On the Deviation Of A Mode I+mentioning
confidence: 99%
See 2 more Smart Citations
“…It also presented that the material's Poisson's ratio and the specimen's thickness affect the three-dimensional evaluation of the biaxiality factor. Gao (1992) analyzed the variation of T n and T 33 along a slightly wavy three-dimensional crack front. The results indicated that the Tn increased with the curvature of the crack front but 7*33 decreased with the crack front curvature.…”
Section: K Tii and 733 And Stress State Around Crack Frontmentioning
confidence: 99%